Physical Mixture Interaction of Acetaminophenol with Naringenin - Normyzatul Akmal Abd Malek; Hamizah Mohd Zaki; Mohammad Noor Jalil (Indonesian Journal of Chemistry, 2018)
The interaction of Active Pharmaceutical Ingredient (API) with other compounds will affect drugs stability, toxicity, modified dissolution profiles or may form a new compound with the different crystal structure. Acetaminophenol (APAP), the most common drug used widely (also known as Panadol) was mixed with Naringenin (NR) to glance for a new phase of interactions leading to new compound phase. The amide-acid supramolecular heterosynthon; N-H…O interaction between acid and the respective base were observed in the APAP-NR mixture blends. The interaction was prepared by the binary interaction from neat grinding and liquid-assisted grinding techniques at a different stoichiometry of binary mixture ratio of APAP-NR which were 1:1, 1:2 and 2:1 molar ratio. The interaction was estimated using Group Contribution Method (GCM) and physicochemical properties were characterized by Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR), powder X-ray diffraction (PXRD) and Differential Scanning Calorimetry (DSC) analysis. The GCM calculation gave good interaction strength at 212.93 MPa1/2. The ATR-FTIR, DSC and PXRD results obtained revealed an interaction with new phase formed.